Evidence based position paper on Physical and Rehabilitation Medicine (PRM) professional practice for ageing people with disabilities. The European PRM position (UEMS PRM Section) - Oral, Aydan; Rapidi, Christina-Anastasia; Votava, Jiri; Roussos, Nikolaos; Michail, Xanthi; Kujawa, Jolanta; Negrini, Stefano; Varela Donoso, Enrique; Christodoulou, Nicolas (European Journal of Physical and Rehabilitation Medicine, 2017)
Ageing people with disabilities (APwDs) are faced with challenges of ageing which is straightforwardly related to disability that adds to the burden related to their early-onset disability. The aim of the paper is to improve Physical and Rehabilitation Medicine (PRM) physicians' professional practice for APwDs (as a distinct group from those who are disabled due to the ageing process) in order to promote their functioning properties and to reduce activity limitations and/or participation restrictions. A systematic review of the literature and a Consensus procedure by means of a Delphi process have been performed involving the delegates of all European countries represented in the UEMS PRM Section. The systematic literature review is reported together with the 30 recommendations resulting from the Delphi procedure. The professional role of PRM physicians in relation to APwDs is extending, expanding and/or improving health-related rehabilitation services worldwide in various settings (getting beyond the rehabilitation facilities) emphasizing the concept of integrated care with collaboration across other sectors to meet the specific needs of APwDs. This evidence based position paper (EBPP) represents the official position of the European Union through the UEMS PRM Section and designates the professional role of PRM physicians in APwDs.
Keywords: European Union; rehabilitační lékařství; hodnocení výsledků zdravotní péče; Risk Assessment; Disease Progression; směrnice pro lékařskou praxi jako téma; postižení; lidé; Professional Practice; senioři nad 80 let; hodnocení rizik; senioři; Evropská unie; mužské pohlaví; Female; Aging; progrese nemoci; Persons with Disabilities; Evidence-Based Practice; Practice Guidelines as Topic; odborná praxe; Male; zdravotní služby pro seniory; Health Services for the Aged; Aged, 80 and over; ženské pohlaví; Aged; Physical and Rehabilitation Medicine; Humans; lidé středního věku; Middle Aged; stárnutí; Outcome Assessment, Health Care; lékařská praxe založená na důkazech